Structural battery based on carbon fiber weaving and preparation method
By adopting carbon fiber braiding technology and nitrogen source coating treatment in lithium-ion batteries, the problem of insufficient energy density and mechanical strength of lithium-ion batteries is solved, and a structural battery with high energy density and high mechanical properties is achieved.
Patent Information
- Application Number
- CN202411859000.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
AI Technical Summary
The energy density of existing lithium-ion batteries cannot meet the requirements of long-term equipment, and their mechanical strength is not enough to meet the high-strength requirements of structural batteries.
Carbon fiber braiding technology is adopted to prepare carbon fiber electrodes by pretreating nitrogen source of carbon fibers and mixing them with positive or negative electrode active materials, then braided into fiber cells, and the structural electrolyte is poured into the battery to obtain a structural battery based on carbon fiber braiding.
The mechanical properties and energy density of structural batteries are improved, the electrode activity is enhanced, the charging and discharge capacity of the battery is improved, and the mechanical strength of the battery is significantly improved through solid electrolyte coating and epoxy resin-based structural electrolyte recombination.
Smart Images

Figure CN119764580A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of structural batteries, and in particular relates to a structural battery based on carbon fiber weaving and a preparation method thereof. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in electrification fields such as new energy vehicles, drones, and intelligent equipment due to their excellent electrochemical properties. They are expected to expand their applications in near-space aircraft and underwater equipment. However, the energy density of lithium-ion batteries currently still cannot meet the requirements of long-term equipment life. In order to solve this problem, researchers are developing batteries with higher energy density on the one hand, and functional batteries that can replace structural parts on the other. If the power system can bear mechanical loads as a structural component, the weight of the entire system will be reduced and the mileage can be extended. The concept of "structural battery" has attracted the attention of researchers and scientific research institutions, which should have sufficient energy density and strong mechanical properties. However, the current lithium-ion batteries are composed of pole pieces, diaphragms, and liquid electrolytes that have almost no mechanical strength, which cannot meet the high strength requirements of structural batteries. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a structural battery based on carbon fiber weaving and a preparation method thereof.
[0004] The technical solution adopted by the present invention is: a method for preparing a structural battery based on carbon fiber weaving, wherein the carbon-based fibers are pretreated by nitrogen source coating, and the coated carbon fibers are respectively mixed with positive electrode active materials or negative electrode active materials to prepare carbon fiber positive electrodes and carbon fiber negative electrodes, and the carbon fiber negative electrodes and carbon fiber positive electrodes are weaved into a fiber battery, and a structural electrolyte is poured into the fiber battery, and encapsulated to obtain a structural battery based on carbon fiber weaving.
[0005] Preferably, the specific preparation method is as follows:
[0006] Carbon-based fiber nitrogen source coating treatment, after calcining the nitrogen-containing compound, dispersed in an organic solvent to form a pretreatment solution, the carbon fiber is placed in the pretreatment solution, ultrasonically and heated to coat the surface of the carbon fiber with the nitrogen source, and calcined to obtain carbon fiber with nitrogen on the surface;
[0007] A negative electrode slurry and a positive electrode slurry are prepared respectively, and carbon fibers containing nitrogen on the surface are immersed in the negative electrode slurry or the positive electrode slurry respectively, and then dried to obtain a carbon fiber negative electrode and a carbon fiber positive electrode;
[0008] mixing an epoxy resin electrolyte containing an epoxy resin, a curing agent and a lithium salt with a liquid electrolyte containing a lithium salt and an electrolyte to form a structural electrolyte;
[0009] The carbon fiber negative electrode and the carbon fiber positive electrode are woven into a two-dimensional structured fiber battery, the fiber battery is infused with a structural electrolyte, and then encapsulated and solidified to form a structural battery based on carbon fiber weaving.
[0010] Preferably, a solid electrolyte slurry containing ceramic powder, a solid electrolyte binder and a non-polar solvent is prepared, and the solid electrolyte slurry is coated on the surface of the carbon fiber negative electrode to obtain a solid electrolyte-coated fiber electrode; the solid electrolyte-coated fiber electrode and the carbon fiber positive electrode are woven into a fiber battery.
[0011] Preferably, the ceramic powder, the solid electrolyte binder and the non-polar solvent are mixed in a mass ratio of 80-100:5-50:50-200;
[0012] Solid electrolyte ceramic powder is Li 1+x Al x Ge 2-x (PO 4 ) 3 , Li 7 La 3 Zr 2 O 12 , Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 , Li 3.25 Ge 0.25 P 0.7 S 4 , Li 6 PS 5 X(X=Cl,Br,I),Li 10 G 2 S 12 One of;
[0013] The solid electrolyte binder is one of ethylene-co-methyl acrylate-glycidyl methacrylate, nitrile rubber (NBR), vulcanized butadiene rubber, and ethylene-methyl methacrylate (EMA) copolymer;
[0014] The non-polar solvent is one of toluene, xylene, tetrahydrofuran, and n-decane;
[0015] Preferably, the carbon fiber negative electrode with the solid electrolyte slurry coated on the surface is dried at 40-120°C.
[0016] Preferably, the nitrogen-containing compound is calcined at 500-600° C. for 2-10 hours under an inert atmosphere, and then ultrasonically dispersed into an organic solvent to form a pretreatment solution. The carbon fiber is placed in the pretreatment solution with an ultrasonic power of 50-400 W, heated at 40-90° C., and then calcined at 700-1000° C. under an inert atmosphere to obtain carbon fiber containing nitrogen on the surface.
[0017] Preferably, the nitrogen-containing compound is one of melamine, dicyandiamide, lysine, phenylalanine and disodium ethylenediaminetetraacetate;
[0018] The organic solvent is one of ethanol, ethylene glycol, isopropanol, toluene, n-butanol, acetone and tetrahydrofuran;
[0019] An inert atmosphere is provided by high purity argon or nitrogen.
[0020] Preferably, a negative electrode material, a negative electrode binder, a conductive agent and a solvent are mixed at a mass ratio of 90 to 120: 1 to 10: 1 to 10: 100 to 200 to obtain a negative electrode slurry; a positive electrode material, a positive electrode binder, a conductive agent and a solvent are mixed at a mass ratio of 90 to 120: 1 to 10: 1 to 10: 100 to 200 to obtain a positive electrode slurry; the negative electrode slurry or the positive electrode slurry is coated on the carbon fiber containing nitrogen on the surface, and then dried at 60 to 120° C. to form a carbon fiber negative electrode or a carbon fiber positive electrode;
[0021] Preferably, the negative electrode material of the lithium-ion battery is one of graphite, niobium-based oxide, lithium titanate, hard carbon material, soft carbon material and their derivatives;
[0022] The lithium ion positive electrode material is one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide and their derivatives;
[0023] The conductive agent is one of carbon nanotubes, conductive carbon black and Ketjen black;
[0024] The negative electrode binder is a mixture of lithium salt and polymer, the mass ratio of the two is 5-100:80-120, the lithium salt is one of LiTFSI, LiClO4, and LiFSI, and the polymer is a mixture of one or more of PVDF, PTFE, PVP, CMC, PEO, PAN, PEGDA, and PETEA;
[0025] The positive electrode binder is a mixture of one or more of PVDF, PTFE, PAA, CMC, PVA, PAN, SBR, and NBR;
[0026] The solvent is one of acetonitrile, N-methylpyrrolidone, toluene and xylene.
[0027] Preferably, epoxy resin, curing agent and lithium salt are mixed in a mass ratio of 50-80:10-40:10-40 to obtain epoxy resin electrolyte; the liquid electrolyte includes lithium salt, electrolyte solvent No. 1 and electrolyte solvent No. 2, the volume ratio of electrolyte solvent No. 1 and electrolyte solvent No. 2 is 30-80:30-80, and the concentration of lithium salt is 0.2-2M; epoxy resin electrolyte and liquid electrolyte are mixed in a mass ratio of 40-80:40-80 to obtain structural electrolyte;
[0028] Preferably, the epoxy resin is one of EP-301, EP-360, EP-365, E-44, E-51, E-54, E-57, E-58, EP-1001, YD-128, ER2221, and EP828AB;
[0029] The curing agent is one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, maleic anhydride, phthalic anhydride, linoleic acid dimer, and eleostearic acid dimer;
[0030] Electrolyte solvent No. 1 and electrolyte solvent No. 2 are any two of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, fluoropropylene carbonate, difluoroethyl acetate, dioxolane glycol dimethyl ether, ethyl acetate, and methyl propionate;
[0031] The lithium salt in the epoxy electrolyte and the liquid electrolyte is the same, specifically lithium perchlorate (LiClO 4 ), lithium hexafluorophosphate (LiPF 6 ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluoroarsenate (LiAsF 6 ) and lithium tetrafluoroborate (LiBF 4 )
[0032] Preferably, the fiber electrode coated with a solid electrolyte or the carbon fiber negative electrode and the carbon fiber positive electrode are connected in parallel in a single or multiple ways, and the positive electrode is stacked on the negative electrode, and the negative electrode is stacked on the positive electrode to continuously weave into a battery with a two-dimensional structure. All the negative electrodes are welded together through nickel tabs, and all the positive electrodes are welded together through aluminum tabs.
[0033] Preferably, the structural electrolyte is poured into the fiber battery, left to stand, and then packaged with an aluminum-plastic film and vacuumed, with the vacuum degree adjusted to -95 to -60 kPa; clamped at a pressure of 0.5 to 2 MPa, and treated at 100 to 150°C for 24 to 48 hours to obtain a structural battery based on carbon fiber weaving.
[0034] A structural battery prepared by a structural battery preparation method based on carbon fiber weaving.
[0035] The advantages and positive effects of the present invention are: by treating the carbon fiber and using a special electrode slurry binder, high adhesion between the electrode active material and the carbon fiber is achieved, which is beneficial to improving the overall mechanical properties of the structural battery when used in the battery; by performing surface N treatment on the carbon fiber, the lithium ions of the structural electrolyte can be quickly desolvated, thereby improving the activity of the electrode and the capacity of the battery;
[0036] By coating the surface of the fiber electrode with a solid electrolyte, not only can the short circuit between the positive and negative electrodes be prevented, but also the transmission efficiency of lithium ions can be improved and the battery capacity can be increased; when encapsulating the battery, the mechanical strength of the battery can be further improved by compounding a high-strength epoxy resin-based structural electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of the preparation process of structural batteries woven with carbon fibers;
[0038] Figure 2 The carbon fiber woven structure is the positive and negative electrode structure inside the battery;
[0039] Figure 3 The actual picture and three-dimensional structure of the structural battery woven with unpackaged carbon fiber; 1. Carbon fiber positive electrode, 2. Carbon fiber negative electrode, 3. Solid electrolyte;
[0040] Figure 4 The actual picture of the carbon fiber woven structure battery after encapsulation and the mechanical performance test;
[0041] Figure 5 Shear strength of structural cells woven from carbon fiber;
[0042] Figure 6 The charge and discharge performance of the battery with a carbon fiber woven structure. DETAILED DESCRIPTION
[0043] The embodiments of the present invention are described below with reference to the accompanying drawings.
[0044] The present invention relates to a structural battery based on carbon fiber weaving and a preparation method thereof. The surface of the carbon fiber is treated to improve the compatibility of the carbon fiber with an electrode slurry. The treated carbon fiber is used as a skeleton to wrap positive and negative electrode active materials to prepare positive and negative electrode fibers respectively, which are further woven into a structural battery.
[0045] Carbon fiber itself has high mechanical strength and can be used as a conductive material or active material for lithium-ion batteries. It is a very promising material. The combination of carbon fiber and structural electrolytes, as well as the positive and negative active materials of lithium-ion batteries, can achieve high strength and high specific energy of the battery. It is necessary to solve the electrochemical compatibility problem between carbon fiber, positive and negative electrode materials of lithium-ion batteries and structural electrolytes, and innovate new composite methods to improve the overall performance of the battery.
[0046] When preparing a structural battery based on carbon fiber weaving, firstly, the carbon-based fiber is pretreated by nitrogen source coating; then the carbon fiber is mixed with positive electrode active material or negative electrode active material to prepare carbon fiber positive electrode and carbon fiber negative electrode; further, the carbon fiber negative electrode is coated with solid electrolyte; the coated carbon fiber negative electrode and carbon fiber positive electrode are woven into a fiber battery, a structural electrolyte is prepared, the structural electrolyte is poured into the fiber battery, and the structural battery based on carbon fiber weaving is encapsulated. The preparation process is as follows: Figure 1 described.
[0047] The specific preparation method is as follows:
[0048] Step 1: Carbon-based fiber pretreatment
[0049] S11: Preparation of nitrogen source, 5-10 g of nitrogen-containing compound is added to a crucible, and in an inert atmosphere, the nitrogen source is obtained by heating the crucible to 500-600° C. at a ventilation rate of 5-15 mL / min and a heating rate of 5-10° C. in a tube furnace for 2-10 hours, wherein the nitrogen-containing compound is one of melamine, dicyandiamide, lysine, phenylalanine and disodium ethylenediaminetetraacetate; and the inert atmosphere is provided by high-purity argon or nitrogen;
[0050] S12: Preparing a pretreatment solution, dispersing the above 0.5-4 g of the nitrogen source in 20-40 mL of an organic solvent by ultrasonication, and ultrasonicating at a power of 200-1000 W for 1-4 h to obtain a pretreatment solution; the organic solvent is one of ethanol, ethylene glycol, isopropanol, toluene, n-butanol, acetone and tetrahydrofuran;
[0051] S13: placing the carbon fiber in a pretreatment solution, treating it with an ultrasonic power of 50 to 400 W for 0.5 to 1.5 h, and then heating it at 40 to 90° C. for 4 to 10 h to uniformly coat the nitrogen source on the surface of the carbon fiber;
[0052] S14: Preparation of carbon fiber containing nitrogen on the surface, placing the carbon fiber uniformly coated with the nitrogen source in the same inert atmosphere as S11, with a ventilation rate of 5 to 15 mL / min and a heating rate of 1 to 5 ° C to 700 to 1000 ° C for 2 to 10 hours to obtain carbon fiber containing nitrogen on the surface. Such carbon fiber containing nitrogen on the surface can promote the desolvation of ions in the structural electrolyte through the interaction of N-electrolyte, thereby improving the charge and discharge capacity of the battery;
[0053] In certain embodiments of the present invention, the carbon fiber may use conventional asphalt-based, PAN-based (such as T300, T700, T800) carbon fiber, which is a continuous fiber material with high mechanical strength, the main component of which is a highly graphitized carbon structure, and can be used as a structural support.
[0054] Step 2: Preparation of carbon fiber negative electrode and carbon fiber positive electrode
[0055] S21: preparing negative electrode slurry, mixing a lithium ion battery negative electrode material, a negative electrode binder and a conductive agent, and a solvent in a mass ratio of 90-120:1-10:1-10:100-200, and mixing in a planetary mixer at a speed of 700-1200 r / min for 30-60 min to obtain a negative electrode slurry;
[0056] S22: preparing positive electrode slurry, mixing a lithium ion battery positive electrode material, a positive electrode binder and a conductive agent, and a solvent in a mass ratio of 90-120:1-10:1-10:100-200, and mixing them in a planetary mixer at a speed of 700-1200 r / min for 30-60 min to obtain a positive electrode slurry;
[0057] The negative electrode material of the lithium-ion battery is one of graphite, niobium-based oxide, lithium titanate, hard carbon material, soft carbon material and their derivatives; the positive electrode material of the lithium-ion battery is one of lithium iron phosphate, lithium cobalt oxide, lithium manganate, nickel cobalt manganate and their derivatives; the conductive agent is one of carbon nanotubes, conductive carbon black and Ketjen black; the negative electrode binder is a mixture containing lithium salt and polymer, the mass ratio of the two is 5-100:80-120, the lithium salt is one of LiTFSI, LiClO4 and LiFSI, and the polymer is a mixture of one or more of PVDF, PTFE, PVP, CMC, PEO, PAN, PEGDA and PETEA; the positive electrode binder is a mixture of one or more of PVDF, PTFE, PAA, CMC, PVA, PAN, SBR and NBR; the solvent is one of acetonitrile, N-methylpyrrolidone, toluene and xylene;
[0058] S23: preparing a carbon fiber negative electrode, immersing the carbon fiber with nitrogen on the surface obtained in step 1 into the negative electrode slurry, and drying it at 60-120° C. for 4-12 hours after the surface is completely covered by the negative electrode slurry to obtain a carbon fiber negative electrode;
[0059] S24: Preparation of carbon fiber positive electrode, immersing the carbon fiber with nitrogen on the surface obtained in step 1 into the positive electrode slurry, after the surface is completely covered by the positive electrode slurry, drying at 60-120° C. for 4-12 hours to obtain the carbon fiber positive electrode.
[0060] Step 3: Solid electrolyte coated fiber electrode
[0061] S31: Preparation of solid electrolyte slurry: solid electrolyte ceramic powder with a particle size of about 200 to 2000 nm, solid electrolyte binder and non-polar solvent are mixed in a mass ratio of 80 to 100: 5 to 50: 50 to 200, and mixed in a planetary mixing tank at a rate of 500 to 1000 r / min for 30 to 60 min to obtain solid electrolyte slurry; wherein the solid electrolyte ceramic powder is Li 1+x Al x Ge 2-x (PO 4 ) 3 , Li 7 La 3 Zr 2 O 12 , Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 , Li 3.25 Ge 0.25 P 0.7 S 4 , Li 6 PS 5 X(X=Cl,Br,I),Li 10 G 2 S 12 The solid electrolyte binder is one of ethylene-co-methyl acrylate-glycidyl methacrylate, nitrile rubber (NBR), vulcanized butadiene rubber, and ethylene-methyl methacrylate (EMA) copolymer; the non-polar solvent is one of toluene, xylene, tetrahydrofuran, and n-decane;
[0062] S32: immersing the carbon fiber negative electrode obtained in step 2 into the solid electrolyte slurry, so that the solid electrolyte slurry is completely coated on the surface of the negative electrode, and further drying the carbon fiber negative electrode with the solid electrolyte slurry on the surface at 40-120° C. for 5-12 hours to obtain a fiber electrode coated with a solid electrolyte;
[0063] Step 4: Preparation of structured electrolyte
[0064] S41: epoxy resin electrolyte preparation, epoxy resin, curing agent, lithium salt are mixed in a mass ratio of 50-80:10-40:10-40, and the mixture is continued to be uniform and set aside; wherein the curing agent is used to cure the epoxy resin; the epoxy resin is one of EP-301, EP-360, EP-365, E-44, E-51, E-54, E-57, E-58, EP-1001, YD-128, ER2221, EP828AB; the curing agent is one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, maleic anhydride, phthalic anhydride, linoleic acid dimer, tungoleic acid dimer;
[0065] S42: liquid electrolyte preparation, lithium salt, electrolyte solvent No. 1 and electrolyte solvent No. 2 are mixed, wherein the volume ratio of electrolyte solvent No. 1 to electrolyte solvent No. 2 is 30-80:30-80, and the concentration of lithium salt is 0.2-2M; electrolyte solvent No. 1 and electrolyte solvent No. 2 are any two of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, fluoropropylene carbonate, difluoroethyl acetate, dioxolane glycol dimethyl ether, ethyl acetate, and methyl propionate;
[0066] The lithium salt in S41 and S42 is the same, which can be lithium perchlorate (LiClO 4 ), lithium hexafluorophosphate (LiPF 6 ), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluoroarsenate (LiAsF 6 ) and lithium tetrafluoroborate (LiBF 4 )
[0067] S43: preparing a structured electrolyte, mixing the epoxy resin electrolyte and the liquid electrolyte obtained in S41 and S42 in a mass ratio of 40-80:40-80 to obtain a structured electrolyte for standby use;
[0068] Step 5: Fiber battery weaving and integrated preparation and packaging
[0069] S51: Fiber battery weaving, the fiber electrode (carbon fiber negative electrode) coated with solid electrolyte and the carbon fiber positive electrode are woven into a battery with a two-dimensional structure in a single or multiple parallel manner, and the structure is a continuous weaving structure of positive electrode on negative electrode and negative electrode on positive electrode, and then all negative electrodes are welded together through nickel tabs, and all positive electrodes are welded together through aluminum tabs;
[0070] S52: Integrated preparation and packaging of fiber batteries. Pour the structural electrolyte into the above fiber battery and let it stand for 10 to 60 hours to fill all the gaps. Then, package it with an aluminum-plastic film and evacuate it. The vacuum degree is adjusted to -95 to -60 kPa. Then, place the battery in an aluminum alloy splint and maintain the pressure at 0.5 to 2 MPa. Then, put it in an oven and treat it at 100 to 150°C for 24 to 48 hours to obtain a structural battery based on carbon fiber weaving.
[0071] By pre-treating the carbon fiber surface, the compatibility of the carbon fiber and the electrode slurry is improved. This surface modification also improves the electrochemical compatibility between the structural electrolyte and the lithium-ion battery, thereby improving the charge transfer dynamics and increasing the battery charge and discharge capacity. In addition, the solid electrolyte is coated on the fiber electrode to alleviate the concentration polarization and achieve a high discharge capacity. Finally, by compounding with an epoxy resin-based structural electrolyte, the mechanical strength of the carbon fiber-based structural battery is greatly improved.
[0072] The scheme of the present invention is described below in conjunction with the accompanying drawings, wherein the experimental methods without specific operating steps are all carried out in accordance with the corresponding product instructions, and the instruments, reagents, and consumables used in the examples can all be purchased from commercial companies unless otherwise specified.
[0073] Example 1
[0074] 1.1 Carbon-based fiber pretreatment
[0075] Take 6.5g of dicyandiamide-containing nitrogen source and add it to the crucible. In a high-purity argon atmosphere, in a tube furnace, keep it at 520℃ for 5h at a ventilation rate of 5mL / min and a heating rate of 5℃ to obtain a nitrogen source; ultrasonically disperse the above 2.5g of nitrogen source in 20mL of ethanol, and ultrasonicate it at a power of 800W for 1.5h to obtain a pretreatment liquid; place the carbon fiber in the pretreatment liquid, and treat it at an ultrasonic power of 180W for 0.5h, and then heat it at 80℃ for 10h to uniformly coat the nitrogen source on the surface of the carbon fiber. Place the carbon fiber uniformly coated with the nitrogen source in a high-purity argon atmosphere, and keep it at 750℃ for 3h at a ventilation rate of 8mL / min and a heating rate of 2.5℃ to obtain a carbon fiber with nitrogen on the surface.
[0076] 1.2 Preparation of carbon fiber negative electrode and carbon fiber positive electrode
[0077] Preparation of carbon fiber negative electrode; Graphite, binder, carbon nanotubes and N-methylpyrrolidone are mixed in a mass ratio of 92:5:3:120, wherein the negative electrode binder is a mixture containing lithium salt and polymer in a mass ratio of 25:85, the lithium salt is LiTFSI, and the polymer is PVP; the mixture is mixed in a planetary mixer at a speed of 1000r / min for 40min to obtain a negative electrode slurry; the carbon fiber with nitrogen on the surface obtained in step 1.1 is immersed in the negative electrode slurry, and after its surface is completely coated with the negative electrode slurry, it is dried at 110°C for 10h to obtain a carbon fiber negative electrode 2;
[0078] Preparation of carbon fiber positive electrode; lithium iron phosphate, PVDF, carbon nanotubes and N-methylpyrrolidone are mixed in a mass ratio of 96:2:2:110, and mixed in a planetary mixer at a speed of 1000r / min for 45min to obtain a positive electrode slurry; the carbon fiber with nitrogen on the surface obtained in step 1.1 is immersed in the positive electrode slurry, and after its surface is completely coated with the positive electrode slurry, it is dried at 110°C for 10h to obtain a carbon fiber positive electrode 1.
[0079] 1.3 Solid electrolyte coated fiber electrode
[0080] Solid electrolyte ceramic powder Li10GeP2S12 with a particle size of about 300 nm, ethylene-methyl methacrylate (EMA) copolymer and toluene were placed in a planetary mixing tank at a mass ratio of 95:5:100 and mixed at a rate of 800 r / min for 30 min to obtain a solid electrolyte slurry;
[0081] The carbon fiber negative electrode 2 obtained in step 1.2 is immersed in the solid electrolyte slurry to completely coat the surface of the carbon fiber negative electrode with the solid electrolyte slurry. The carbon fiber negative electrode with the solid electrolyte slurry on the surface is further dried at 80°C for 8 hours to obtain a fiber electrode coated with a solid electrolyte 3.
[0082] 1.4 Preparation of structured electrolytes
[0083] Epoxy resin E-51, phthalic anhydride and lithium perchlorate bistrifluoromethanesulfonyl imide (LiTFSI) were mixed in a mass ratio of 70:20:20, and mixed until uniform to obtain an epoxy resin electrolyte for later use;
[0084] Lithium perchlorate bis(trifluoromethanesulfonyl)imide (LiTFSI), propylene carbonate and methyl propionate are uniformly mixed to prepare a liquid electrolyte, wherein the volume ratio of propylene carbonate to methyl propionate is 75:25, and the lithium salt concentration is 1.5 M;
[0085] The epoxy resin electrolyte and liquid electrolyte prepared above were mixed evenly at a mass ratio of 50:50 to obtain a structural electrolyte for later use.
[0086] 1.5 Fiber battery preparation and integrated manufacturing and packaging
[0087] The fiber electrode (containing the carbon fiber negative electrode 2) coated with the solid electrolyte and the carbon fiber positive electrode 1 are woven into a battery with a two-dimensional structure in a single or multiple parallel connection, wherein the structure is a continuous woven structure of positive electrode on negative electrode and negative electrode on positive electrode, and then all the negative electrodes are welded together through nickel tabs and all the positive electrodes are welded together through aluminum tabs to obtain a fiber battery, wherein the structure is as follows: Figure 2 As shown, the final physical picture is as follows Figure 3 As shown;
[0088] The structural electrolyte is poured into the above fiber battery and allowed to stand for 48 hours to fill all the gaps. It is then packaged with an aluminum-plastic film and vacuumed to -95 kPa. The battery is then placed in an aluminum alloy clamp and the pressure is maintained at 0.7 MPa. It is then placed in an oven and treated at 110 ° C for 36 hours. The aluminum alloy clamp is then removed and the battery is repackaged to obtain a structural battery based on carbon fiber weaving, such as Figure 4 shown.
[0089] Further mechanical tests were conducted on the structural battery, which showed high shear strength. The shear strength of the structural battery based on carbon fiber weaving is as follows: Figure 5 As shown, it is shown that the structural battery has the ability to bear loads and thus acts as a structural member.
[0090] Example 2
[0091] 2.1 Carbon-based fiber pretreatment
[0092] 6.5 g of the nitrogen-containing compound dicyandiamide was added to a crucible, and in a high-purity argon atmosphere, the temperature was raised to 580°C in a tube furnace at a ventilation rate of 5 mL / min and a heating rate of 5°C for 2 h to obtain a nitrogen source; 1.5 g of the nitrogen source was ultrasonically dispersed in 30 mL of ethanol, and ultrasonicated at a power of 250 W for 1 h to obtain a pretreatment solution; the carbon fiber was placed in the pretreatment solution, and ultrasonically treated at a power of 150 W for 0.5 h, and then heated at 80°C for 6 h to evenly coat the nitrogen source on the surface of the carbon fiber;
[0093] The prepared carbon fiber uniformly coated with nitrogen source was placed in a high-purity argon atmosphere, with a ventilation rate of 6.5 mL / min and a heating rate of 3.5 °C to 780 °C and maintained for 2.5 h to obtain carbon fiber with nitrogen on the surface. This carbon fiber with nitrogen on the surface can promote the desolvation of ions in the structural electrolyte through the interaction of N-electrolyte, thereby improving the charge and discharge capacity of the battery.
[0094] 2.2 Preparation of carbon fiber negative electrode and carbon fiber positive electrode
[0095] Preparation of carbon fiber negative electrode: Graphite, binder, conductive carbon black and N-methylpyrrolidone are mixed in a mass ratio of 92:4:4:120, the negative electrode binder is a mixture containing lithium salt and polymer, the mass ratio of the two is 30:80, the lithium salt is LiTFSI, and the polymer is a mixture of PVDF and PVP in a mass ratio of 1:1; the above mixture is mixed in a planetary mixer at a speed of 1000r / min for 40min to obtain a negative electrode slurry; the carbon fiber with nitrogen on the surface obtained in step 2.1 is immersed in the negative electrode slurry, and after the surface is completely coated with the negative electrode slurry, it is dried at 80°C for 12h to obtain a carbon fiber negative electrode;
[0096] Preparation of carbon fiber positive electrode: lithium nickel cobalt manganese oxide, PVDF, conductive carbon black and N-methylpyrrolidone are mixed in a mass ratio of 97:1.5:1.5:110, and mixed in a planetary mixer at a speed of 100 r / min for 40 min to obtain a positive electrode slurry; the carbon fiber with nitrogen on the surface obtained in step 2.1 is immersed in the positive electrode slurry, and after its surface is completely coated with the positive electrode slurry, it is dried at 110°C for 8 h to obtain a carbon fiber positive electrode.
[0097] 2.3 Solid electrolyte coated fiber electrode
[0098] Solid electrolyte ceramic powder Li with a particle size of about 300nm 3.25 Ge 0.25 P 0.7 S 4 , solid electrolyte binder and xylene in a mass ratio of 96:4:120 are placed in a planetary mixing tank and mixed at a rate of 800r / min for 40min to obtain a solid electrolyte slurry; the solid electrolyte binder is ethylene-acrylic acid comethyl ester-methacrylate glycidyl;
[0099] The carbon fiber negative electrode obtained in step 2.2 is immersed in the solid electrolyte slurry to completely coat the surface of the negative electrode with the solid electrolyte slurry. The carbon fiber negative electrode with the solid electrolyte slurry on the surface is further dried at 110°C for 5 hours to obtain a solid electrolyte-coated fiber electrode.
[0100] 2.4 Preparation of structured electrolytes
[0101] Epoxy resin E-57, curing agent phthalic anhydride and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) are mixed in a mass ratio of 50:20:20, wherein the curing agent is used to cure the epoxy resin; the mixture is continued to be mixed until uniform to obtain an epoxy resin electrolyte for standby use;
[0102] Mixing lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), ethylene carbonate and fluoroethylene carbonate, wherein the volume ratio of ethylene carbonate to fluoroethylene carbonate is 45:55 and the concentration of lithium salt is 1.2 M; and obtaining a liquid electrolyte;
[0103] The epoxy resin electrolyte and the liquid electrolyte are uniformly mixed in a mass ratio of 60:40 to obtain a structural electrolyte for standby use.
[0104] 2.5 Fiber battery weaving and integrated preparation and packaging
[0105] The solid electrolyte coated fiber electrode (negative electrode) and the carbon fiber positive electrode are woven into a battery with a two-dimensional structure in a single or multiple parallel connection, wherein the structure is a continuous woven structure of positive electrode on negative electrode and negative electrode on positive electrode, and then all the negative electrodes are welded together through nickel tabs and all the positive electrodes are welded together through aluminum tabs to obtain a fiber battery;
[0106] The structural electrolyte is poured into the above-mentioned fiber battery and left to stand for 48 hours to fill all the gaps. It is then packaged with an aluminum-plastic film and evacuated to -95kPa. The battery is then placed in an aluminum alloy splint and the pressure is maintained at 0.7MPa. It is then placed in an oven and treated at 130°C for 24 hours. At this time, the epoxy resin in the structural electrolyte is cured, giving the battery a rigid structure with high mechanical strength. The aluminum alloy splint is then removed and the battery is repackaged to obtain a structural battery based on carbon fiber weaving.
[0107] Example 3: Battery performance experiment
[0108] The structured battery prepared in Example 2 was compared with the unmodified structured battery. The preparation process of the unmodified structured battery is basically similar to that of the battery in Example 2, except that the nitrogen source treatment process in step 2.1 and the solid electrolyte coating fiber electrode process in step 2.3 are missing. The carbon fiber negative electrode and the carbon fiber positive electrode are directly prepared using untreated carbon fiber, and the prepared carbon fiber negative electrode and carbon fiber positive electrode are directly woven to form a fiber battery.
[0109] Connect the battery to the replay point tester and set the voltage to 2.8~4.3V. The charge and discharge performance of the two are as follows: Figure 6 As shown, compared with the unmodified structural battery (without carbon fiber pretreatment and solid electrolyte coating), the structural battery based on carbon fiber weaving exhibits higher charge and discharge capacity.
[0110] The embodiments of the present invention are described in detail above, but the contents described are only preferred embodiments of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a structural battery based on carbon fiber weaving, characterized in that: The carbon-based fibers are pretreated by nitrogen source coating, and the coated carbon fibers are respectively mixed with positive electrode active materials or negative electrode active materials to prepare carbon fiber positive electrodes and carbon fiber negative electrodes, the carbon fiber negative electrodes and carbon fiber positive electrodes are woven into fiber batteries, and the structural electrolyte is poured into the fiber batteries, and encapsulated to obtain a structural battery based on carbon fiber weaving.
2. The method for preparing a structural battery based on carbon fiber weaving according to claim 1, characterized in that: The specific preparation method is as follows: Carbon-based fiber nitrogen source coating treatment, after calcining the nitrogen-containing compound, dispersed in an organic solvent to form a pretreatment solution, the carbon fiber is placed in the pretreatment solution, ultrasonically and heated to coat the surface of the carbon fiber with the nitrogen source, and calcined to obtain carbon fiber with nitrogen on the surface; A negative electrode slurry and a positive electrode slurry are prepared respectively, and carbon fibers containing nitrogen on the surface are immersed in the negative electrode slurry or the positive electrode slurry respectively, and then dried to obtain a carbon fiber negative electrode and a carbon fiber positive electrode; mixing an epoxy resin electrolyte containing an epoxy resin, a curing agent and a lithium salt with a liquid electrolyte containing a lithium salt and an electrolyte to form a structural electrolyte; The carbon fiber negative electrode and the carbon fiber positive electrode are woven into a two-dimensional structured fiber battery, the fiber battery is infused with a structural electrolyte, and then encapsulated and solidified to form a structural battery based on carbon fiber weaving.
3. The method for preparing a structural battery based on carbon fiber weaving according to claim 2, characterized in that: A solid electrolyte slurry containing ceramic powder, a solid electrolyte binder and a non-polar solvent is prepared, and the solid electrolyte slurry is coated on the surface of the carbon fiber negative electrode to obtain a solid electrolyte-coated fiber electrode; the solid electrolyte-coated fiber electrode is woven with the carbon fiber positive electrode to form a fiber battery.
4. The method for preparing a structural battery based on carbon fiber weaving according to claim 3, characterized in that: The ceramic powder, the solid electrolyte binder and the non-polar solvent are mixed in a mass ratio of 80-100:5-50:50-200; Solid electrolyte ceramic powder is Li 1+x Al x Ge 2-x (PO4)3, Li7La3Zr2O 12 , Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li 3.25 Ge 0.25 P 0.7 S4, Li6PS5X (X=Cl, Br, I), Li 10 GeP2S 12 One of; The solid electrolyte binder is one of ethylene-co-methyl acrylate-glycidyl methacrylate, nitrile rubber, vulcanized butadiene rubber, and ethylene-methyl methacrylate copolymer; The non-polar solvent is one of toluene, xylene, tetrahydrofuran, and n-decane; Preferably, the carbon fiber negative electrode with the solid electrolyte slurry coated on the surface is dried at 40-120°C.
5. The method for preparing a structural battery based on carbon fiber weaving according to claim 2 or 3, characterized in that: The nitrogen-containing compound is calcined at 500-600° C. for 2-10 hours under an inert atmosphere, and then ultrasonically dispersed into an organic solvent to form a pretreatment solution. The carbon fiber is placed in the pretreatment solution and heated at 40-90° C. with an ultrasonic power of 50-400 W, and then calcined at 700-1000° C. under an inert atmosphere to obtain carbon fiber containing nitrogen on the surface. Preferably, the nitrogen-containing compound is one of melamine, dicyandiamide, lysine, phenylalanine and disodium ethylenediaminetetraacetate; The organic solvent is one of ethanol, ethylene glycol, isopropanol, toluene, n-butanol, acetone and tetrahydrofuran; and the inert atmosphere is provided by high-purity argon or nitrogen.
6. The method for preparing a structural battery based on carbon fiber weaving according to claim 2 or 3, characterized in that: A negative electrode material, a negative electrode binder, a conductive agent and a solvent are mixed at a mass ratio of 90 to 120: 1 to 10: 1 to 10: 100 to 200 to obtain a negative electrode slurry; a positive electrode material, a positive electrode binder, a conductive agent and a solvent are mixed at a mass ratio of 90 to 120: 1 to 10: 1 to 10: 100 to 200 to obtain a positive electrode slurry; after coating the negative electrode slurry or the positive electrode slurry on the surface of nitrogen-containing carbon fiber, drying at 60 to 120° C. to form a carbon fiber negative electrode or a carbon fiber positive electrode; Preferably, the negative electrode material of the lithium-ion battery is one of graphite, niobium-based oxide, lithium titanate, hard carbon material, soft carbon material and their derivatives; The lithium ion positive electrode material is one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel cobalt manganese oxide and their derivatives; The conductive agent is one of carbon nanotubes, conductive carbon black and Ketjen black; The negative electrode binder is a mixture of lithium salt and polymer, the mass ratio of the two is 5-100:80-120, the lithium salt is one of LiTFSI, LiClO4, and LiFSI, and the polymer is a mixture of one or more of PVDF, PTFE, PVP, CMC, PEO, PAN, PEGDA, and PETEA; The positive electrode binder is a mixture of one or more of PVDF, PTFE, PAA, CMC, PVA, PAN, SBR, and NBR; The solvent is one of acetonitrile, N-methylpyrrolidone, toluene and xylene.
7. The method for preparing a structural battery based on carbon fiber weaving according to claim 2 or 3, characterized in that: The epoxy resin, the curing agent and the lithium salt are mixed in a mass ratio of 50-80:10-40:10-40 to obtain an epoxy resin electrolyte; the liquid electrolyte includes a lithium salt, an electrolyte solvent No. 1 and an electrolyte solvent No. 2, the volume ratio of the electrolyte solvent No. 1 to the electrolyte solvent No. 2 is 30-80:30-80, and the concentration of the lithium salt is 0.2-2M; the epoxy resin electrolyte and the liquid electrolyte are mixed in a mass ratio of 40-80:40-80 to obtain a structural electrolyte; Preferably, the epoxy resin is one of EP-301, EP-360, EP-365, E-44, E-51, E-54, E-57, E-58, EP-1001, YD-128, ER2221, and EP828AB; The curing agent is one of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, maleic anhydride, phthalic anhydride, linoleic acid dimer, and eleostearic acid dimer; Electrolyte solvent No. 1 and electrolyte solvent No. 2 are any two of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, fluoropropylene carbonate, difluoroethyl acetate, dioxolane glycol dimethyl ether, ethyl acetate, and methyl propionate; The lithium salt in the epoxy resin electrolyte and the liquid electrolyte is the same, specifically one of lithium perchlorate, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium hexafluoroarsenate and lithium tetrafluoroborate.
8. The method for preparing a structural battery based on carbon fiber weaving according to claim 2 or 3, characterized in that: The fiber electrode or carbon fiber negative electrode coated with solid electrolyte is connected with the carbon fiber positive electrode in a single or multiple parallel manner, and the positive electrode is continuously woven with the negative electrode and the negative electrode is continuously woven with the positive electrode into a battery with a two-dimensional structure. All the negative electrodes are welded together through nickel tabs, and all the positive electrodes are welded together through aluminum tabs.
9. The method for preparing a structural battery based on carbon fiber weaving according to claim 8, characterized in that: The structural electrolyte is poured into the fiber battery, allowed to stand, and then packaged with an aluminum-plastic film and vacuumed to a vacuum degree of -95 to -60 kPa; clamped at a pressure of 0.5 to 2 MPa, treated at 100 to 150 ° C for 24 to 48 hours to obtain a structural battery based on carbon fiber weaving.
10. A structural battery prepared by the method for preparing a structural battery based on carbon fiber weaving as described in any one of claims 1 to 9.